Unidirectional all-oxide mini-composites with crack-deflecting NdPO4 interface - Kaya, C.; Butler, E. G. (ELSEVIER SCI LTD, 2009)
Unidirectional Nextel 720 (TM) fibers were coated with crack-deflecting NdPO4 interface using dip coating and infiltrated with silica-free alumina matrix using electrophoretic deposition followed by drying and pressureless sintering at 1200 degrees C in an attempt to manufacture oxide-based model 'mini-composites' which are less complex to produce in a short time and which therefore allow rapid results for mechanical and microstructural characterisation. This material is targeted for use at 1200 degrees C in an oxidising atmosphere and has shown an excellent tensile strength value of 1.2 GPa and flexural strengths of 894 MPa at room temperature and 761 MPa at 1300 degrees C in unidirectional form. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Composites; Al2O3; Interface; Mini-composites; NdPO4; CERAMIC-MATRIX COMPOSITES; ELECTROPHORETIC DEPOSITION; DAMAGE-TOLERANT; FABRICATION; INFILTRATION; Materials Science